Synthesis of 18F‐Difluoromethylarenes from Aryl (Pseudo) Halides. Issue 36 (5th August 2016) - Shi, Hang; Braun, Augustin; Wang, Lu; Liang, Steven H.; Vasdev, Neil; Ritter, Tobias
Abstract: A general method for the synthesis of [ 18 F]difluoromethylarenes from [ 18 F]fluoride for radiopharmaceutical discovery is reported. The method is practical, operationally simple, tolerates a wide scope of functional groups, and enables the labeling of a variety of arenes and heteroarenes with radiochemical yields (RCYs, not decay‐corrected) from 10 to 60 %. The 18 F‐fluorination precursors are readily prepared from aryl chlorides, bromides, iodides, and triflates. Seven 18 F‐difluoromethylarene drug analogues and radiopharmaceuticals including Claritin, fluoxetine (Prozac), and [ 18 F]DAA1106 were synthesized to show the potential of the method for applications in PET radiopharmaceutical design. Abstract : PET peeve resolved : A general method for the synthesis of [ 18 F]CHF2 ‐arenes from [ 18 F]fluoride enables labeling of a variety of arenes and heteroarenes with radiochemical yields (not decay‐corrected) from 10 to 60 %. The 18 F‐fluorination precursors are readily prepared from aryl chlorides, bromides, iodides, and triflates. Seven 18 F‐difluoromethylarene drug analogues and radiopharmaceuticals were synthesized to show the potential of the method.